Reeleição e eficiência educacional nos municípios nordestinos - Santana, Andre Moreira Araujo de (2025)
The efficiency of educational management can be significantly impacted by political factors, particularly the re-election of mayors. The administrative continuity provided by re-election can allow for greater stability in the implementation of public policies and efficiency gains in education management. This dissertation investigates the relationship between re-election and educational efficiency in municipalities in the Northeast of Brazil, using a panel data model with differences-in-differences. The study focused on primary education in these municipalities during the years 2009, 2011, 2013, and 2015. The results indicate that re-election has a positive effect on educational efficiency, with an average increase of 0.03 percentage points. This finding reinforces the idea that re-elected mayors can consolidate more effective educational policies, ensuring the continuity of investments and long-term strategies. Furthermore, re-election can reduce disruptions in project execution and the loss of institutional capital, essential factors for educational progress. The results of this study highlight the relevance of re-election as a potential mechanism for improving educational efficiency, emphasizing the importance of administrative continuity and institutional learning in enhancing education quality.